Workers in health, the forgotten actors by reform’s - Carrasco-Cortez, Víctor (2014)
The health reform has gained a new momentum in Peru, because via legislative decrees, wants to implement a series of changes which have been called improperly "health care reform", because it does not alter fundamentally the structure and functioning of our exclusionary and segmented system. In this context, it becomes relegated to postpone key actorsof the reforms, namely: workers health. The evidence of this are persistence of: the lack of government in the field of human resources, centralist and inequitable distribution, the precariousness of employment, rising occupational health problems, high migration, the deregulation of training and professional practice in the Peru. It is urgent to meet the challenges set for the Decade of human resources in health 2006-2015.